Stories of change : transforming lives through agricultural and rural development (CTA AJ WageningenNL, 2014)
Provides a snapshot of CTA's achievements during the last decade. Provides an insight into the broad range of activities that CTA has supported through partnerships across Africa, the Caribbean and the Pacific (ACP).
Keywords: AGRICULTURE